Pollen carriers of Cocos nucifera L. (Palmae) in Costa Rica and Ecuador (Neotropical region) - Hedström, Ingemar (Revista de Biología Tropical, 1986)
Potential pollinating insects of the coconut palm, Cocos nucifera L. (Palmae), were identified in Cahuita National Park, Barbilla Biological Reserve, Pacuarito de Siquirres, Guácimo and Bribrí, Province of Limón, and in Turrúcares and La Garita, Province of A lajuela, Costa Rica. Observations were also conducted in Guayaquil and Cerecita, Province of Guayas, Ecuador. The most common pollen carrier in Costa Rica was Trigona silvestriana Vachal, followed by T. testacea Klug, T. fulviventris Guérin, T. frontalis Friese, T. tataira Smith, T. corvina Cockerell, Melipona fasciata Latreille, all stingless meliponid bees, and the honeybee Apis mellifera L. In Ecuador, A. mellifera was observed visiting both staminate and pistillate flowers of C. nucifera. Observations on interference competition between some of the species of Trigona from Costa Rica are also presented.